Colonization of Western Sahara - Besenyő, János (Études sur la Région Méditerranéenne, 2011)
In this article, I’d like to write a short analysis about the colonization of Western Sahara because as a candidate for a doctor’s degree, I’m making some research about the UN peacekeeping mission in Western Sahara (MINURSO). I think, that we have to see a global picture when we make a research about any peace keeping, peace support or peace enforcement mission, because without the background of the conflict, we can’t get a correct view. Up till now altogether - including me - 20 Hungarian officers and approximately this many police officers have served in the mission. Maybe that is why, and also due to the lack of concrete Hungarian interests the Hungarian Defence Forces have relatively few information on this territory and the developments here. Nowadays, a small Hungarian contingent (7 people) serves in MINURSO. However, nobody made any analysis about the Western Sahara case till today. Only I made some small articles in various newspapers previously. For this reason I chose this theme to make a dissertation about MINURSO and the Western Sahara case. In Western Sahara, there is a long time clash between the real inhabitants of the land (named Sahrawians) and the newcomers from Morocco. Unfortunately, it is not so easy to understand the conflict, if we don’t know the history of this land, especially about the Spanish colonization and their role in this conflict. Hopefully, this article will give some idea for the readers about this matter. But first I’d like to share some basic information about Western Sahara.